Myth as an Islamic Symbolic Defense: A Historical-Symbolic Study of the Myth of Gong Gerem in Pringsurat Village, Temanggung Regency - Panis Dhbi Salam (Faculty of Ushuluddin, Adab, and Humanities Universitas Islam Negeri Salatiga, 2024)
This research is motivated by intellectual anxiety towards the mainstream understanding of myth studies. Myths have always been understood in terms of education or if not so, then in terms of truth which cannot be trusted scientifically. However, this study will look at the gong gerem myth as a cultural symbolic phenomenon, thus allowing for different interpretation. The method used in this study is the historical method, which includes heuristics, source criticism, interpretation and historiography. The paradigm used is symbolic with the assumption that culture is a symbolic phenomenon, which can be given meaning. The meaning built in this context relates it to the historical and socio-cultural conditions of the supporting community. The results of this study show that the myth of gong gerem in the forms of wewaler (prohibition) and balak (disaster) contains Islamic symbolic messages for the Ngloho and Bleder people. Wewaler that contains a prohibition against people not performing arts using a gong because it can cause floods, contains a message that they are not allowed to engage in the art of jogedan because they are considered to distract people from God. However, when this type of art finally became available in that place, disaster (read balak) is believed to have come in the form of the breakdown of the santri's moral order. Therefore, the myth of gong gerem in the form of wewaler and balak is basically a symbolic defense of Islamic society.